A review of recent progress toward development of a formulated microbound diet for mud crab, Scylla serrata, larvae and their nutritional requirements - Holme, May-Helen; Zeng, Chaoshu; Southgate, Paul C. (Aquaculture, 2009)
This article presents an overview of recent progress on the nutrition of Scylla serrata larva and its implications in feed formulation. Recently published results of dietary trials with S. serrata larvae have helped build a basic framework of knowledge concerning the dietary requirements of this species, and these advances will undoubtedly upgrade hatchery production which traditionally has depended heavily on live food such as rotifers and Artemia nauplii. However, many aspects of larvae mud crab nutrition is still not fully understood and further studies are required in order to develop an optimized diet. The purpose of this review is to summarize the information that has been published to date, and to highlight areas where more research is needed. Key subjects are assessed under the following major headings; problems associated with use of live food in larval culture; development of a formulated diet for hatchery production of S. serrata larvae; and nutritional requirements for protein, lipid and carbohydrates.